Bibliografia relaţiilor literaturii române cu literaturile străine în periodice - Carmen Brăgaru (Revista de Istorie și Teorie Literară)
The present study is a survey of one of the oldest, longest and most thorough projects ran over the years in “G. Călinescu” Institute of Literary History and Theory of the Romanian Academy. Bearing the title Bibliografia relaţiilor literaturii române cu literaturile străine în periodice (The Bibliography Regarding the Relations Between the Romanian Literature and the Literatures of the World in Periodical Publications), the project has arrived at the third series. The first one gathering three volumes published during the ’80s covers the period between 1859 and 1918, the second one gathering 10 volumes published in the late ’90s and the beginning of the 2000s covers the period between 1919 and 1944, while the work on the third series focused on the period between 1945 and 1964 is in progress. The first part of the study follows closely the history of Romanian bibliographies of all kind as our project is a younger branch of the vigorous tree planted by the Romanian Academy back in the 1890s. The second part of the study dealing with our Bibliography itself is also divided in many chapters regarding the history of the project in the Institute, the researchers involved during the four decades of activity, a thorough description of the three series, the methodology and the challenges for each stage, the plans for the future. Emphasizing the difference between the original and unique bibliographical project of “G. Călinescu” Institute and other types of bibliographies, such as enumerative, descriptive, analytical or textual ones, the presentation ends with a selective list of articles, studies and books inspired by the Bibliography, as well as the most important echoes and impact the project had in the cultural media.